2021
DOI: 10.1108/rsr-04-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Is the library open? How the pandemic has changed the provision of virtual reference services

Abstract: PurposeThe purpose of this paper is to investigate the impact of the pandemic on the questions received via chat reference at a Canadian university library.Design/methodology/approachA qualitative analysis using coding of chat transcripts and a quantitative analysis of the length of chat interactions were used in this study.FindingsThe author determined that the types of questions received changed slightly during the pandemic due to the new library services offered. The complexity level of questions did not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Dempsey (2016) identified that 50% of chat interactions were reference questions, while Fennewald (2006) reported that 72% of chat questions at their institution can be classified as reference. Previous research at the authors' institutions reported that reference questions were present in 14–24% of interactions (Hervieux, 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Dempsey (2016) identified that 50% of chat interactions were reference questions, while Fennewald (2006) reported that 72% of chat questions at their institution can be classified as reference. Previous research at the authors' institutions reported that reference questions were present in 14–24% of interactions (Hervieux, 2021).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Although it is a popular approach, other researchers preferred to use an established coding scheme to compare their results with other institutions. The READ scale has proven to be a popular coding scheme to determine the level of complexity of reference interactions (Gerlich and Berard, 2010; Hervieux, 2021; Maloney and Kemp, 2015; Mawhinney and Hervieux, 2022). Other researchers have also proposed coding to determine the presence of instruction in reference (Desai and Graves, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Acertadamente el servicio de chat se pone en operación en diciembre de 2017 siendo bastante esencial durante el periodo de la pandemia por el virus sars-CoV-2 (covid-19) y consolidándose como uno de los servicios digitales de dgbsdi al momento de la emisión del acuerdo emitido por el rector de la unam (Graue, 2020), en donde la Dirección General de Bibliotecas cambia su nombre por el de Dirección General de Bibliotecas y Servicios Digitales de Información, con el al ser un servicio tan inmediato para consultar y para pedir ayuda; ha contribuido para que el estudiante se atreva a establecer contacto con la ayuda brindada por la biblioteca digital, en lugar de tener que desplazarse o llamar por teléfono (Hervieux, 2021), el crecimiento que se vio mayormente reflejado de acercamiento fue mayor en niveles de licenciatura y bachillerato.…”
Section: Digitales De Informaciónunclassified
“…As it pertains to physical library closures as necessitated by the COVID-19 pandemic, McGill University Libraries did report an increase in the number of virtual reference questions received as well as an increase in the length of those interactions online, particularly around midterms and finals (Hervieux, 2021). Similarly, the College of Staten Island Library reported an increase in the use of virtual services related to pandemic closures and moved to alter the schedule to include longer virtual shifts for chat operators and the method of monitoring their chat queues in order to provide better targeted service to their users (Garvey, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%